Konsep Muhammad Abduh Tentang Islam Rasional Di Era Modern - Harry Mulfi (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2021)
Muhammad Abduh was born in Mahallat District village, Al-Bahirah province in 1266 H / 1849 AD and died in 1322 H / 1905 AD Muhammad Abduh was a scholar and well-known Reformist figure in modern times. He is an intellectual who wants modernization efforts for the rise of modern Islam. Abduh wanted an Islam based on rationality in order to release Muslims from the shackles of imitation, static, and old age which were the main causes of the decline of the ummah.            Muhammad Abduh for him, Islam is a rational religion. religions that have a harmonious relationship with the ratio, complement each other and that cannot be separated. Rationalism is the only method that can lead every Muslim to the way to obtain truth, peace and true faith. Not only that, rationalism can also make Muslims excel in advances in science and technology.            Muhammad Abduh in his term Al-Aqlaniyah Al Islamiyah, namely Islamic rationality, is against the skepticism which is anti-reason and exaggeration of reasoning. Ummah should not be satisfied simply standing on the gate of a text without maximizing the potential of the ratio in mengintrepetasikan implied meaning and interpretation in the Qur'an. In conclusion, Muhammad Abduh wanted to create a modern Islamic civilization that excelled in the advancement of science and technology by maximizing the potential ratio based on the Al-Qur'an (Allah) and Hadith (Rasul).